Autologous peripheral blood mononuclear cells as treatment in refractory acute respiratory distress syndrome - Jungebluth, Philipp (Respiration, 2015)
Acute respiratory distress syndrome (ARDS) is a devastating disorder. Despite enormous efforts in clinical research, effective treatment options are lacking, and mortality rates remain unacceptably high. Objectives: A male patient with severe ARDS showed no clinical improvement with conventional therapies. Hence, an emergent experimental intervention was performed. Methods: We performed intratracheal administration of autologous peripheral blood-derived mononuclear cells (PBMCs) and erythropoietin (EPO). Results: We found that after 2 days of initial PBMC/EPO application, lung function improved and extracorporeal membrane oxygenation (ECMO) support was reduced. Bronchoscopy and serum inflammatory markers revealed reduced inflammation. Additionally, serum concentration of miR-449a, b, c and miR-34a, a transient upregulation of E-cadherin and associated chromatin marks in PBMCs indicated airway epithelial differentiation. Extracellular vesicles from PBMCs demonstrated anti-inflammatory capacity in a TNF-a-mediated nuclear factor-κB in vitro assay. Despite improving respiratory function, the patient died of multisystem organ failure on day 38 of ECMO treatment. Conclusions: This case report provides initial encouraging evidence to use locally instilled PBMC/EPO for treatment of severe refractory ARDS. The observed clinical improvement may partially be due to the anti-inflammatory effects of PBMC/EPO to promote tissue regeneration. Further studies are needed for more in-depth understanding of the underlying mechanisms of in vivo regeneration.